Synthesis of polyynes using dicobalt masking groups. - Kohn, D; Gawel, P; Xiong, Y; Christensen, K; Anderson, H (American Chemical Society, 2018)
Extended triisopropylsilyl end-capped polyynes have been prepared from the corresponding tetracobalt complexes by removing the complexed dicobalt tetracarbonyldiphenylphosphinomethane (Co2(CO)4dppm) moieties. Unmasking of this 'masked alkyne equivalent' was achieved under mild conditions with elemental iodine at room temperature, making it possible to obtain fragile polyynes with up to 20 contiguous sp-hybridized carbon atoms. The Co2(CO)4dppm moiety has a strong geometric and steric effect on the polyyne, but does not have a marked electronic effect on the terminal alkyne, as indicated by NMR and IR spectroscopy, density functional theory calculations and X-ray crystallography. An unusual 'alkyne hopping' migration of the dicobalt group was noticed, as a minor side reaction during copper-catalyzed Eglinton coupling.